Examining the Conditions of the Possible Adoption of the Greek Philosophical Heritage at the Beginning of the Establishment of Philosophy in the Islamic World - Mahdi Ataaii; Abasaleh Taqizadeh Tabari (حکمت اسرا, 2013)
The present research seeks to discuss the emergence of the Islamic philosophy in the Islamic world by means of the concept of conditions for adoption. Of course what is investigated in this paper is the possibility of the adoption of the Greek philosophical heritage in the Islamic philosophy during its onset. In other words, the attempt is made here to realize under what conditions Muslim intellectuals faced the Greek philosophical heritage and were, then, able to absorb such heritage and make it their own. An understanding of such conditions in that historical era, and if we are able to understand the Muslim philosophers, will open new possibilities for our condition today and for our relations with the western human sciences and in order to establish Islamic human sciences. To this end, it will be shown that “seeking the truth” and “considering thinking by means of thinking” have been among the most important conditions that made the establishment of the Islamic philosophy, by means of the Greek philosophical heritage, possible.